2022
DOI: 10.3389/fvets.2022.899901
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Chicken Astrovirus Related Illnesses

Abstract: Of the several known viruses, chicken astrovirus (CAstV) has been associated with diarrhea, runting-stunting syndrome, severe kidney disease, and gout, and white chick syndrome (WCS) in young broiler chicks. Discovered in 2004, CAstV consists of two genogroups with an expanding subgroup because of the diversity exhibited in its viral capsid sequence. Despite these findings, there exists a dearth of knowledge on its pathogenesis. This review highlights the pathogenesis and development of in vivo and in vitro mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 67 publications
(104 reference statements)
0
8
0
Order By: Relevance
“…As the most divergent region of the CAstV genome, ORF2 gene encodes capsid precursor proteins of the viral particle, which is the major determinant of virus antigenicity, immune response, cell tropism and viral pathogenicity ( Smyth et al, 2012 ; Raji and Omar, 2022a , b ). CAstV strains, based on phylogenetic analysis and the genetic distance of the ORF2 amino acid sequences, can be divided into two distinct genogroups (A and B): Group A with three subgroups (Ai, Aii, and Aiii), and Group B consists of six subgroups (Bi, Bii, Biii, Biv, Bv, and Bvi) ( Smyth, 2017 ; Raji et al, 2022 ; Raji and Omar, 2022a , b ). The previous studies have reported that diverse CAstV strains (subgroup Ai, subgroup Bi, subgroup Bii) are detected circulating in Chinese chicken flocks ( Zhao et al, 2020 ; Luan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As the most divergent region of the CAstV genome, ORF2 gene encodes capsid precursor proteins of the viral particle, which is the major determinant of virus antigenicity, immune response, cell tropism and viral pathogenicity ( Smyth et al, 2012 ; Raji and Omar, 2022a , b ). CAstV strains, based on phylogenetic analysis and the genetic distance of the ORF2 amino acid sequences, can be divided into two distinct genogroups (A and B): Group A with three subgroups (Ai, Aii, and Aiii), and Group B consists of six subgroups (Bi, Bii, Biii, Biv, Bv, and Bvi) ( Smyth, 2017 ; Raji et al, 2022 ; Raji and Omar, 2022a , b ). The previous studies have reported that diverse CAstV strains (subgroup Ai, subgroup Bi, subgroup Bii) are detected circulating in Chinese chicken flocks ( Zhao et al, 2020 ; Luan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chicken astrovirus (CAstV), belonging to genus Avastrovirus in Astroviridae family, acts as an etiologic agent of enteric disease in chickens, and makes a primarily effect on the poultry industry, and generates economic losses worldwide ( Raji and Omar, 2022a , b ). CAstV is a star-shaped morphology (28–30 nm in diameter), non-enveloped, positive-sense, and single-stranded RNA virus ( Smyth, 2017 ; Raji and Omar, 2022a , b ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations